Analyzing the Needs and Trends in The Macro Environment - Hapsawati Taan (Journal of International Conference Proceedings (JICP), 2019)
Successful companies usually recognize and respond to needs and trends that have not been met with profit. This paper aims to discuss the needs and trends in the company's main macro environment, namely: demography, economy, nature, technology, politicslaw, and socio-cultural. Marketers try to create new solutions to unmet needs. Many opportunities are found by identifying trends (direction or sequence of events that have a certain momentum and time period). The conclusion of this paper is that the rapidly changing global situation of marketers / companies must monitor six major environmental forces namely: demography, economy, nature, technology, politics-law, and sociocultural.